CNS-LAND score: predicting early neurological deterioration after intravenous thrombolysis based on systemic responses and injury - Jin, Huijuan; Bi, Rentang; Zhou, Yifan; Xiao, Qinghui; Li, Min; Sun, Shuai; Zhou, Jinghua; Hu, Jichuan; Huang, Ming; Li, Yanan; Hong, Candong; Chen, Shengcai; et al. (Frontiers in Neurology, 2023)
Importance: Early neurological deterioration (END) is a critical complication in acute ischemic stroke (AIS) patients receiving intravenous thrombolysis (IVT), with a need for reliable prediction tools to guide clinical interventions. Objective: This study aimed to develop and validate a rating scale, utilizing clinical variables and multisystem laboratory evaluation, to predict END after IVT. Design, Setting, and Participants: The Clinical Trial of Revascularization Treatment for Acute Ischemic Stroke (TRAIS) cohort enrolled consecutive AIS patients from 14 stroke centers in China (Jan 2018 to Jun 2022).Outcomes: END defined as NIHSS score increase >4 points or death within 24 hours of stroke onset.Results: 1,213 patients (751 in the derivation cohort, 462 in the validation cohort) were included. The CNS-LAND score, a 9-point scale comprising seven variables (CK-MB, NIHSS score, systolic blood pressure, LDH, ALT, neutrophil, and D-dimer), demonstrated excellent differentiation of END (derivation cohort C statistic: 0.862; 95% CI: 0.796-0.928) and successful external validation (validation cohort C statistic: 0.851; 95% CI: 0.814-0.882). Risk stratification showed END risks of 2.1% vs. 29.5% (derivation cohort) and 2.6% vs. 31.2% (validation cohort) for scores 0-3 and 4-9, respectively. Conclusions: CNS-LAND score is a reliable predictor of END risk in AIS patients receiving IVT.